Treatment of Methicillin-Resistant Staphylococcus aureus (MRSA) Pneumonia with Ceftaroline Fosamil in a Patient with Inhalational Thermal Injury. Issue 4 (December 2015) - Faris, Janie; Mynatt, Ryan; Hall Snyder, Ashley; Rybak, Michael
Abstract A 48-year-old female, who was found unresponsive and suffered inhalation injury secondary to a house fire, was transferred to our burn center for definitive treatment. Post tracheostomy, the patient became febrile and tachycardic. On hospital day (HD) 5, the patient expressed thick yellow secretions during suctioning and diffuse rhonchi was noted on physical exam. Blood cultures and a culture from the broncheo-alvelolar lavage grew Gram-positive cocci in clusters and the patient was started on empiric vancomycin. Despite aggressive vancomycin dosing (1750 mg intravenously every 6 h), the patient's status continued to deteriorate. The organism was identified as methicillin-resistantStaphylococcus aureus (MRSA) with a vancomycin minimum inhibitory concentration (MIC) of 2 mg/L. Based on the potential for drug–drug interactions with linezolid, the patient was started on ceftaroline fosamil (MIC = 0.5 mg/L) 600 mg intravenously every 8 h with a prolonged 2-h infusion to anticipate suboptimal concentrations secondary to thermal burn injury. Post change in antibiotic therapy, a rapid clinical improvement was observed with the patient becoming afebrile at 48 h after initiation of ceftaroline. The patient completed a total of 14 days of ceftaroline therapy and was subsequently weaned from the ventilator on HD 22 and decannulated 2 days later. To our knowledge, this is the first report of the use of ceftaroline for the treatment of MRSA pneumonia in a patient with thermal injury.